(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The MRI process can be a challenging experience for young children. Therefore, general anaesthesia is often used to ensure paediatric patient’s compliance. A recent attempt by researchers and practitioners has been the development of mobile applications that are designed to provide a virtual real-like MRI experience. The paper aims to review and provide insight into some of the available MRI mobile applications regarding their functionality and use as well as providing practical suggestions for future mobile application developers in the field. MRI mobile applications that are available on the two platforms of IOS and Android were downloaded and tested to gain the user experience in terms of functionality and overall use. The findings revealed that the available MRI mobile applications designed for the paediatric community lack features and functionalities in terms of appealing to the age groups they had been designed for. Such features include the lack of availability of interactive games, aesthetic layouts, localisation to suit the culture, lack of dual language, etc. The review of the available MRI mobile applications that are designed for paediatric users clearly showed that more work should be done and there is a room for improvement in terms of their designs and functionality.